Global, regional and national retinoblastoma burden in children under 10 years of age from 1990 to 2021: Trend analysis based on the Global Burden of Disease Study 2021 - Siqi Zhang; Guoxin Huang; Xiang Li; ZhiJie Zhang; KaiXin Peng; Lei Zhu; Chengda Zhang; Tong-tong Niu (PLoS ONE, 2025)
Background Retinoblastoma (RB) is the most common malignant eye tumor in children, which poses a great threat to children’s vision and life. Comprehensive global, regional and country-level assessments of retinoblastoma in children under 10 years of age are important to help fine-tune health policies and rationalize the allocation of medical resources. Methods Data on RB-related burden in children under 10 years of age were collected in the 2021 Global Burden of Disease (GBD) study to assess trends in RB burden using mean annual percentage change (AAPC). Absolute and relative health inequalities of RB burden were analyzed using slope index and concentration index. An age-period-cohort model was fitted using package NORDPRED to predict the future RB burden. Results The global number of RB cases in children under 10 years of age in 2021 was 57,333 (95%UI: 34339.65,761.03), the annual standardized prevalence rate (ASPR) was 4.39(95%UI: 2.63, 5.95), and the AAPC (1990−2021) was 0.65(95%CI: 0.44, 0.86). Over the past 30 years, age-standardised mortality (ASMR) and age-standardised DALY(ASDR) have declined globally. At the level of socio-demographic index (SDI) regions, ASIR and ASPR were the highest in the medium-high SDI and high SDI regions, with ASPR being 6.03(95%UI: 3.01–9.21) and 5.44(95%UI: 3.97–7.18), and ASIR being 0.66(95%UI: 0.33–1.01) and 0.59(95%UI: 0.43–0.78). The mortality and DALYs of RB decreased gradually with the increase of SDI. At the country level, China and India are the countries with the highest number of cases, together accounting for about 30% of the global cases, and ASIR is still on the rise in these two countries. The inequality analysis shows that RB burden is heavier in countries with lower SDI. The number of RB cases worldwide is expected to rise slowly, but the global burden will gradually decrease. Conclusion As one of the main causes affecting the life and health of children, with the increase in the number of diseases worldwide, it is necessary for decision-makers to customize relevant intervention policies to provide effective prevention and control measures to help achieve the global Sustainable Development Goals.